A NavPress Bible study on the book of Proverbs (Life change series, 1990)
A NavPress Bible study emphasizing: personal discovery of God's Word; Application of Scripture to your daily life; Scene-setting historical insights; Mini leader's guides for small groups; Helpful word origins and definitions; Stimulating discussion questions; Challenging optional projects.